Does the labour relations act unjustifiably limit the constitutional right of employees to freedom of assembly? Examining the constitutionality of the prohibition on purely political protest action and gatherings by off-duty employees over disputes of mutual interest - Allsop, Geoffrey Charles (Department of Commercial Law, 2020)
This thesis examines whether the Labour Relations Act 66 of 1995 (‘LRA’) justifiably limits the constitutional right to employees to freedom of assembly in accordance with s36(1) of the Constitution of the Republic of South Africa, 1996 (‘the Constitution’). This question is considered in two broad parts. The first part demonstrates two limitations. First, the inability of s77 of the LRA to provide legislative protection to employees who wish to embark on socioeconomic protest action over a purely political issue. Second, the LRA’s prohibition on off-duty employees utilising the Regulation of Gatherings Act 205 of 1993 (‘RGA’) to demonstrate against their employer over a dispute of mutual interest. While no court has yet considered if the LRA prohibits purely political protest action, the Labour Appeal Court in ADT Security v NASUWU 2015 (36) ILJ 152 (LAC) (‘ADT Security’) held that is unlawful for off-duty employees to demonstrate over a dispute of mutual interest under the RGA. The first part begins by establishing how the LRA’s statutory definition of protest action cannot, in its current form, protect purely political protest and how this limits the constitutional right of employees to free assembly. Similarly, it explains how ADT Security clearly establishes that the LRA limits the constitutional right of employees to freedom of assembly by infringing their constitutional right to assemble and demonstrate in compliance with the RGA. The second part tests both limitations against s36(1) of the Constitution, the limitation clause, to assess if either infringement justifiably limits the constitutional right of employees to freedom of assembly, enshrined in s17 of the Bill of Rights. Considering the factors in s36(1)(a)-(e) of the Constitution, and other relevant factors, it examines if the purpose and reasons for either limitation are sufficiently compelling so as to be reasonable and justifiable. It concludes by arguing both limitations unjustifiably limit the constitutional right of employees to free assembly. Two recommendations are made. First, that the LRA be amended to expressly permit employees to demonstrate over disputes of mutual interest, in compliance with the RGA, in certain circumstances. Second, that the LRA be amended to expressly permit purely political protest action, provided the protest action is limited in scope and duration and subject to oversight by the Labour Court.